A Handy Detection Tool to Recognise DCNP (Nerve Gas Mimic) in Sea Water and Soil: An Awareness to Make a Better Environment - Shampa Kundu; Shrabani Saha; Prithidipa Sahoo (New Innovations in Chemistry and Biochemistry Vol. 7, 2022)
The main objective of this research work is to design and synthesis of some novel chemosensors which are highly sensitive and selective for the detection of some toxic elements in aqueous medium. The toxic elements become hazardous to the whole ecosystem through their ability of binding with vital cellular components, such as structural proteins, enzymes, and nucleic acids, and interfering with their functional activities. In consequence, a reliable, facile and reactive detection method of such hazardous species, is of great global interest towards the development of practical ‘in field’ devices. Nerve agents are very toxic organophosphorus compounds. Thanks to their deadly activity towards the human and animal health, they're used as chemical welfare agents; closely connected compounds are used enormously within the chemical industry. Sea-dumping is taken into account united of the standard ways of disposal of those chemical weapons, however this might introduce a fatal consequence adore disruption of marine eco-system and inclusion of these reactive and cyanogenic substances into food chain. To detect the nerve gas we developed a very simple and low cost paper strip sensing method which can immediately recognize DCNP in visual range. A chemosensor, carbazole-salicylaldehyde based imine (CSI), has been introduced for selective detection and quantification of nerve gas (Tabun) mimic DCNP from sea water and soil in nanomolar range at neutral pH (pH 7.2, 10 mM Tris-HCl buffer).